Clinical care of childhood sexual abuse: a systematic review and critical appraisal of guidelines from European countriesResearch in context - Gabriel Otterman; Ulugbek B. Nurmatov; Ather Akhlaq; Laura Korhonen; Alison M. Kemp; Aideen Naughton; Martin Chalumeau; Andreas Jud; Mary Jo Vollmer Sandholm; Eva Mora-Theuer; Sarah Moultrie; Diogo Lamela; et al. (Elsevier, 2024)
Summary: Background: The clinical management of Child sexual abuse (CSA) demands specialised skills from healthcare professionals due to its sensitivity, legal implications, and serious physical health and mental health effects. Standardised, comprehensive clinical practice guidelines (CPGs) may be pivotal. In this systematic review, we examined existing CSA national CPGs (NCPGs) from European countries to assess their quality and reporting. Methods: We systematically searched six international databases and multiple grey literature sources, reporting by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) standards. Eligible guidelines were CSA guidance from national health agencies or societies in 34 COST Action 19106 Network Countries (CANC), published between January 2012 and November 2022. Two independent researchers searched, screened, reviewed, and extracted data. NCPGs were compared for completeness with reference WHO 2017 and 2019 guidelines. We used the Appraisal of Guidelines for Research and Evaluation (AGREE II) to appraise quality and reporting. PROSPERO: CRD42022320747. Findings: Of 2919 records identified by database searches, none met inclusion criteria. Of 4714 records identified by other methods, 24 NCPGs from 17 (50%) of CANC countries were included. In 17 (50%) of eligible countries, no NCPGs were found. Content varied significantly within and between countries. NCPGs lacked many components in state-of-the art clinical practice compared to WHO reference standards, particularly in safety and risk assessment, interactions with caregivers, and mental health interventions. Appraisal by AGREE II revealed shortcomings in NCPG development, regarding scientific rigour, stakeholder involvement, implementation and evaluation. Interpretation: A notable number of European countries lack an NCPG; existing NCPGs often fall short. The healthcare response to CSA in Europe requires a coordinated approach to develop and implement high-quality CPGs. We advocate for a multidisciplinary team to develop a pan-European CSA guideline to ensure quality care for survivors. Funding: Funding was provided by the International Centre for Missing and Exploited Children.